Model hierarchies in space-mapping optimization: Feasibility study for transport processes - Marheineke, Nicole; Pinnau, René (Journal of Computational Methods in Sciences and Engineering, 2012)
The space mapping technique aims at an efficient optimization of complex technical problems. Its success relies on the quality of the coarse model that might be deduced from either physical, algebraic or grid-based hierarchies of models. In this paper we perform a feasibility study for transport processes coming from the fields of fluid dynamics, semiconductors and radiation. We present appropriate model hierarchies and discuss the numerical performance. Space mapping shows to give very convincing suboptimal solutions to the actual fine model optimization regarding the balance of computational effort (speed and memory) and accuracy. © 2012 - IOS Press and the authors. All rights reserved.
Keywords: Aggressive space mapping; flow control; optimal control; radiation optimization; semiconductor design